EFEKTIVITAS KINERJA PEJABAT STRUKTURAL DALAM ORGANISASI MITRA PEMERINTAH KABUPATEN BANDUNG - Sugih Candra Kayat; Purwanti Basuki (STISIP Widyapuri Mandiri, 2025)
Structural officials in partner organizations of the Bandung Regency government play a strategic role in managing and developing regional sports. This study aims to analyze their performance effectiveness and identify supporting factors and challenges faced. Using a descriptive qualitative approach, the findings indicate that performance effectiveness is influenced by individual competence, government policies, and collaboration with sports stakeholders. However, challenges such as budget constraints, complex bureaucracy, and a lack of innovation remain major obstacles. To enhance effectiveness, strategies such as capacity building for human resources, optimizing cross-sector coordination, and leveraging technology in sports governance are necessary.